Abnormal TNS3 gene methylation in patients with congenital scoliosis - YuanTao Wu; Hong-qi Zhang; Mingxing Tang; Chaofeng Guo; Shaohua Liu; Jiong Li; Yunjia Wang; Lige Xiao; Guanteng Yang (BMC Musculoskeletal Disorders, 2022)
Abstract Background Congenital scoliosis (CS) is a congenital deformity of the spine resulting from abnormal and asymmetrical development of vertebral bodies during pregnancy. However, the etiology and mechanism of CS remain unclear. Epigenetics is the study of heritable variations in gene expression outside of changes in nucleotide sequence. Among these, DNA methylation was described first and is the most characteristic and most stable epigenetic mechanism. Therefore, in this study, we aim to explore the association between genome methylation and CS which are not been studied before. Methods Two pairs of monozygotic twins were included, with each pair involving one individual with and one without CS. Agilent SureSelect XT Human Methyl-Sequencing was used for genome methylation sequencing. MethylTarget was used to detect methylation levels in target regions. Immunohistochemistry was performed to visualize expression of associated genes in candidate regions. Results A total of 75 differentially methylated regions were identified, including 24 with an increased methylation level and 51 with a decreased methylation level in the CS group. Nine of the differentially methylated regions were selected (TNS3, SEMAC3, GPR124, MEST, DLK1, SNTG1, PPIB, DEF8, and GRHL2). The results showed that the methylation level of the promoter region of TNS3 was 0.72 ± 0.08 in the CS group and 0.43 ± 0.06 in the control group (p = 0.00070 < 0.01). There was no significant difference in the degree of methylation of SEMAC3, GPR124, MEST, DLK1, SNTG1, PPIB, DEF8, or GRHL2 between the two groups. Immunohistochemistry showed significantly decreased TNS3 expression in the cartilage of the articular process in CS (CS: 0.011 ± 0.002; control: 0.018 ± 0.006, P = 0.003 < 0.01). Conclusion Compared with the control group, high-level methylation of the TNS3 promoter region and low TNS3 expression in the cartilage layer of the articular process characterize CS. Thus, DNA methylation and TNS3 may play important roles in the pathogenesis of CS.